OPTIMALISASI KEBERSIHAN DIRI DAN PENYULUHAN KEBERSIHAN DIRI DAN CUCI TANGAN PADA SISWASISWI DI SD BABAKAN III KECAMATAN CIPARAY KABUPATEN BANDUNG - Ira Ocktavia Siagian (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2019)
Community service activities carried out in Babakan Village, Ciparay District, Bandung Regency are community service activities that become the annual agenda of the Immanuel College of Health Sciences in Bandung. In 2018, the Nursing D3 study program focuses community service activities at Babakan III Elementary School. The target of these community service activities is for students in grades 1 through 6. The aim of community service is to increase the knowledge of SD Babakan III students about personal hygiene, and to know the optimization of personal hygiene. Method: This activity was carried out in SD Babakan III using a community empowerment approach. The intended community is elementary school students in Babakan III, Ciparay Subdistrict, especially classes 3 and 4, as many as 85 students were trained for 2 days. The form of training provided is through the provision of material with lectures, discussions and demonstrations. Results: Based on the evaluation in the form of pre-test and posttest, there was an increase in students' knowledge, from 60% to 90%. This training also provides enrichment about personal hygiene for class teachers in SD Babakan III, Ciparay District. Conclusion: This training was conducted at SDN Babakan III with a total of 85 students, with a good level of knowledge (90%) after 2 days of training. It is hoped that the training that has been carried out will be able to become the foundation for behavior change in the school environment and at home by applying the principles of healthy living.